The influence of dietary energy level on the response to betaine - M G Young; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
A total of 800 pigs were used to evaluate the influence of dietary energy level on the response to betaine in finishing pig diets. Dietary treatments were arranged in a 2 × 2 factorial with or without betaine and two energy density levels as the main effects. No betaine × energy interactions (P>0.05) were observed for the entire feeding period (51 to 210 lb) or for any of the three dietary phases. Pigs fed the high energy diets with added fat had (P<.05) greater ADG, lower ADFI, and improved F/G compared with pigs fed the low energy diets without added fat. Adding betaine to the diet had no influence on pig performance.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Betaine; Energy; Finishing pigs